An introduction to proton beam therapy. (2nd October 2019) - Barker, Claire; Lowe, Matthew; Radhakrishna, Ganesh
Abstract : Radiotherapy is a highly effective anti-cancer treatment commonly used alongside systemic therapies and surgery to achieve long-term cancer-free survival. Conventional radiotherapy uses photon beams to deliver a high dose of radiation to the tumour volume to eradicate cancer cells. This has to be offset against the irradiation of surrounding normal tissues, as increasing this dose causes more treatment-related toxicity. In August 2018, the NHS's first high energy proton beam therapy centre opened at The Christie NHS Foundation Trust in Manchester. A second NHS centre is scheduled to open in 2020 at the University College London Hospitals NHS Trust. Proton beam therapy may offer dosimetric advantages compared to conventional radiotherapy as a result of its characteristic dose deposition – proton beams deliver a comparatively higher proportion of their dose to the target volume relative to normal tissues, without significant exit doses when compared to conventional photon therapy. Therefore proton beam therapy may be indicated for certain tumours situated next to critical organs or in the paediatric population where quality of life and the reduction of secondary effects from radiation are particularly significant. The indications for proton beam therapy and patient outcomes after treatment will be carefully monitored and evaluated in order to provide a robust evidence base for its use.